Clinical Trial of Black Seeds Against COVID – 19 in Kirkuk City/ Iraq - Kadhim Ali Abbas Al-Haidari; TunjaiNamiq Faiq; OzdanAkram Ghareeb (Institute of Medico-legal Publications Pvt Ltd, 2021)
In order to cope with Coronavirus Disease 2019 (COVID-19) pandemic, there is an urgent need for effectiveprevention and control measures. This study aims to explore the positive action of black seeds (BS) againstCOVID-19 in patients involved in the trail. It is a descriptive, comparative, and open-label study. In ourstudy, (419) participants were divided into two groups.The studied participants included patients whichreceived standard care treatment as a control group (CON) , while the (BS) group were patients receivedblack seeds at a 40 mg/kg dose orally, once daily for 14 days plus standard protocol of treatment. Theevidence of BS efficacy was obvious in the severity and outcome of infection with covid-19. A significantlyhigher severity of infection among control group 44 (17.0%) than the black seed group were noticed; thecontrol group also showed 14 deaths (5.4%), while there were no deaths in black seeds group (0.0%). Thus,we can conclude that black seed is very effective in reducing the severity of covid-19 and preventing deathin infected patients.